MARKETING COMMUNICATIONS FOR UMKM IN KLAMBIR 5 KEBON, HAMPARAN PERAK, DELI SERDANG, NORTH SUMATERA - Roro Rian Agustin; Rindi Andika (Sean Institute, 2023)
Marketing communication has a key role in shaping the brand image and in increasing the sales of a brand. The tight competition situation, technological developments, and changes in consumer behavior make marketers have to implement integrated marketing communications. Brand placement strategy is one of the strategies in integrated marketing communications. This strategy is considered more effective than advertising communication strategies through television media. The concept of brand placement strategy has existed for a long time and continues to develop along with the development of human civilization. By studying, understanding and implementing these strategies, companies can maximize their resources to achieve marketing communication goals effectively and efficiently.